Identifikasi Produk Unggulan Daerah Propinsi Daerah Istimewa Yogyakarta - Ibnu Wahid Fakhrudin Aziz (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2000)
This research was done for identifying domestic superior analysis (product unggulan daerah) through establishing the strategic indicator criterias and weighted strategic indicators. The strategic indicators were developed cord on Directorat General Regional Development (Dirjen Bangda) decision number : 050.05/30/Bangda tanggal 07-01-1999 and fromMinistry of Industrial and Trade (DEPPERINDAG). The strategic indicators and their weighed factors are : Export (25 %), Local contains in product (20 %), labor (20 %), value added (10 %), linkage (10 %), marketing reached (10 %) and environment (5 %). The composition that resulted from data, calculation and justification are 52 potential product, with sequence 5 highest potential product : Volatile oil, meubelair / household set, craft (beside bamboo), bamboo craft, and chips made from cassava and flour. Related the policy of province government with Kecamatan as Center of Economical Growth, so many superior product in there, such as volatile oil in Kec Samigaluh and meubelair in Kec Godean, so this related can be increased in the future there. All of product are superior product, but the sequence of product explanation nowadys, and can be hope to increasing of performance and positif growth for industry. The sequence of potential product can be comprehensive topics for the government to design industrial and commodity policy whether domestic autonomy in the future.